Multiple sclerosis: relationship between locus of control and quality of life in persons with low versus high disability. Issue 1 (31st December 2022) - Bijoux Leist, Judith; Leist, Thomas P.
ABSTRACT: Background: Health Locus of Control (HLOC) is the degree to which individuals believe that their health outcomes are controlled by 'external' factors – environmental forces, chance, fate, other people, or some higher power – or by 'internal' factors – their own behavior or action. Most of the literature on HLOC associates an Internal Health Locus of Control (IHLOC) to pro-health behaviors and better health outcomes. However, a few studies also suggest that in chronic illnesses, an External Health Locus of Control (EHLOC) could be beneficial with respect to pro-health behaviors and perceptions of Quality of Life (QoL), challenging assumptions about what leads to the most effective psychological coping in the face of difficult circumstances. Multiple sclerosis (MS) is a chronic immune condition of the central nervous system and the most frequent cause of non-traumatic disability in young adults, often despite treatment. Method: The primary goal of this non-experimental, cross-sectional, quantitative study of 89 individuals with MS was to explore the HLOC of individuals with MS, and to identify whether holding an EHLOC positively impacts the MS patients' perceived QoL while taking into consideration their level of disability. Results: This research found that individuals with higher disability scores tended to hold more EHLOC beliefs, and that there was a significant correlation between QoL and holding EHLOC beliefs. Conclusion: This study was able to capture the importance of control beliefs in the QoL of individuals with MS with higher disability. The clinical implications of the findingare explored and areas for further research are suggested.